Effect of Smoking on Some Biochemical and Hematological Indicators in Smokers - Yaseen, Oras Khalis; Kudhair, Inam Hussein (American Journal of Biomedicine and Pharmacy, 2025)
Objective: The aim of our study is to investigate the effect of smoking on hematological levels, lipid profile, renal and liver function tests, and cardiac enzymes in current smokers. Materials and Methods: This investigation was conducted in various locations within Diyala Province, Iraq, from January to April 2024. A total of 100 blood samples were collected from smokers and 50 samples from non-smokers, which served as the control group. HbA1C was measured using a Biorex machine (Denmark), and hemoglobin (Hb) and platelets (PLTs) were measured using a Hematology Analyzer (CBC machine) (India). Serum concentrations of fasting blood sugar (FBS), blood urea, serum creatinine, lipid profile, ALT, AST, ALP, and high-sensitivity cardiac troponin (hs-cTn) markers were determined using a Roche Cobas e411 (Switzerland). The SPSS v. 20.0 program was used to analyze our data at a significance level of P≤0.05. Results: The outcomes of the current study showed that most smokers were within the age groups 31-40 (35%) and 21-30 years (30%), with fewer in the age groups 51-60 (12%) and >60 years (9%), showing significant differences among age groups (p<0.05). Additionally, we found a significant increase (p<0.05) in the levels of hemoglobin, platelets, cholesterol, triglycerides, ALT, AST, ALP, hs-cTn, and creatinine in smokers compared to non-smokers. In contrast, the study revealed no significant differences (p>0.05) in the levels of HbA1c and urea between smokers and non-smokers. Conclusions: This investigation suggests that chronic cigarette smoking increases blood levels of hemoglobin, platelets, serum creatinine and urea, lipid profile, and cardiac and liver enzymes. These elevated levels may be associated with a higher risk of atherosclerosis, polycythemia vera, chronic obstructive pulmonary disease, and/or cardiovascular diseases. Recommendations: The current study recommends conducting further research on the effects of smoking on biochemical variables in smokers and those who quit smoking, compared to non-smokers.